ASUHAN KEBIDANAN BERKELANJUTAN PADA NY.S, NY.A, NY.A DI PMB DESI ARIANI, S.Tr.Keb - DWI YANTI (LPPM STIKes Mitra Adiguna, 2023)
Efforts that can be made to suppress MMR and IMR are by carrying out Continuity of Care checks. Continuity of Care care is continuous care from pregnancy to family planning as an effort to reduce MMR and IMR. Services achieved in Continuity of Care Care are when there is a continuous relationship between a mother and a midwife. The aim of the report is to provide Continuing Midwifery Care starting from pregnancy, childbirth, postpartum, BBL and family planning with complementary midwifery care during the postpartum period by providing the Oxytocin Massage technique to increase milk production in Mrs.S, Ny. A and Mrs. A. The method used in Continuity of Care care is a type of descriptive research using a case study approach. The results of the report obtained from Continuity of Care care were given complementary oxytocin massage therapy to the three patients with the same therapy on the first day of therapy given an observation sheet (pretest) with results < 5 which were included in the Less ASI category and were evaluated on the seventh day given a post sheet test with results > 5 which is included in the sufficient ASI category. The conclusion of this report is that after carrying out oxytocin massage care for Mrs. S, Mrs. A, and Mrs. A experienced an increase in milk production and found no gaps between theory and practice.